Toxic Consciousness and Discourse in Don DeLillo’s White Noise - Jabar Mohammed, Bahman; Dler Ameen , Mohammed; Othman Arif , Kawan (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The study explores two themes in Don DeLillo’s White Noise. The first one is toxic consciousness suggested by Cynthia Deitering in her article "The Post natural Novel," the other one is toxic discourse theorized by Lawrence Buell in an article under the same title. The researchers argue that White Noise embodies both of these themes and offers a change in American identity. The researchers use analytical and ecocritical approaches to identify that both themes account for the concerns DeLillo expresses in the novel. It is important to note that both Deitering and Buell’s ideas are influenced by Martin Heidegger’s concept of "standing reserve," presented in his article in 1953. The study concludes that the novel is an important text in raising the awareness of American public and authority alike about the spread of toxicity in their society. In addition, it also works as a discourse for addressing the same question.